Hubungan Antara Analisis Jabatan dan Kepuasan Kerja - Putri Oktaviani; Netty Merdiaty (Global Leadership Organizational Research in Management, 2025)
The era of globalization requires organizations to increase competitiveness through the improvement of human resources (HR). The factor of increasing human resources is job satisfaction. Job satisfaction is an important element needed by employees, so position analysis is one of the determinants of job satisfaction. This study aims to find out the relationship between job analysis and employee job satisfaction. Used the Systematic Literature Review (SLR) method to review 10 relevant scientific articles and journals from the last five years. The results of the study show that job title analysis has a significant influence on job satisfaction. The placement of employees according to their competencies increases work comfort and productivity. In addition, job satisfaction is also influenced by other factors, such as organizational culture, training, and leadership style. This research provides insight for organizations in managing human resources, especially through the application of effective position analysis.